PELATIHAN BANTUAN HIDUP DASAR (BHD) PADA KADER SIAGA BENCANA DI KELURAHAN PARUPUAK TABING PADANG: Basic Life Support (BHD) Disaster preparedness Cadres in Parupuk Tabing Padang - Puteri Nabilla; Susmiati Susmiati; Dewi Murni (LPPM Universitas Abdurrab, 2023)
Basic life support (BLS) knowledge is crucial for the general public because emergencies can happen at any time and anywhere, especially in locations at high risk of natural disasters. Due to its location on the coastline, Parupuk Tabing Village is a disaster-prone place, hence disaster mitigation is necessary to reduce the impact of disasters. The goal of this service is to use BHD procedures in RW 17 Parupuak Tabing and to provide nursing care to village disaster preparedness cadres (K2SB). The approach involves counseling along with giving nursing care. The sample consists of 13 K2SB participants. Total sampling is the sampling method used. Measurements of knowledge levels were done before and after BHD training. The evaluation results showed thethe evaluation results; itit was observed that the pre-test results typically lacked knowledge (84.6%) and moderate knowledge (15.4%). In contrast, the results of the post-test knowledge were generally good (92.3%) and moderate knowledge (7.7%). It is advised to engage in additional activities to develop the abilities needed to do basicl life support, one of which is frequent training.